2007
DOI: 10.1063/1.2432953
|View full text |Cite
|
Sign up to set email alerts
|

Ferrite-ferroelectric hybrid wave phase shifters

Abstract: A dual, electric and magnetic field tunable microwave phase shifter based on the propagation of hybrid spin-electromagnetic waves in a ferrite-ferroelectric bilayer is discussed. The bilayer consists of a single-crystal yttrium iron garnet film and a ceramic barium strontium titanate slab. The electrical tunability of the differential phase shift Δφ is achieved through the application of a voltage across barium strontium titanate. An insertion loss of 20dB and a continuously variable Δφ as high as 650° in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(72 citation statements)
references
References 11 publications
1
71
0
Order By: Relevance
“…A ferrite-ferroelectric layered structure, such as a ME composite, opens up the possibility of dual-tunable microwave devices, which offers higher efficiency, lower noise, compact size and lightweight compared to conventional microwave deceives. Following theoretical investigations, Ustinov et al [122] reported the development of such ME devices. Their ME dual phase shifter based on FMR is a bilayer ME composite consisting of a ferrite YIG layer with a thickness of 5.7 μm and a ferroelectric BST layer with a thickness of 500 μm.…”
Section: Phase Shiftersmentioning
confidence: 99%
“…A ferrite-ferroelectric layered structure, such as a ME composite, opens up the possibility of dual-tunable microwave devices, which offers higher efficiency, lower noise, compact size and lightweight compared to conventional microwave deceives. Following theoretical investigations, Ustinov et al [122] reported the development of such ME devices. Their ME dual phase shifter based on FMR is a bilayer ME composite consisting of a ferrite YIG layer with a thickness of 5.7 μm and a ferroelectric BST layer with a thickness of 500 μm.…”
Section: Phase Shiftersmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Multiferroic composites consisting of ferro/ferrimagnetic and ferroelectric phases are widely recognized to be able to realize electric field control of magnetic order due to its strong strain mediated magnetoelectric ͑ME͒ coupling resulting from the inversed piezoelectric effect and piezomagnetic effect. [10][11][12][13][14][15][16][17][18][19] Several multiferroic heterostructures have been known to show large electrical field manipulation of magnetism, such as FeGaB/Si/PMN-PT ͑lead magnesium niobate-lead titanate͒, yttrium iron garnet ͑YIG͒/PMN-PT and YIG/BSTO ͑barium strontium titanate͒, 8,10,11,20,21 which show great prospects for E-field tunable magnetic devices. However, the tunable ranges of most demonstrated microwave multiferroic devices are still quite limited.…”
Section: Introductionmentioning
confidence: 99%
“…27 Compared to conventional tunable microwave magnetic devices that are tuned by magnetic field, these electrostatically tunable microwave multiferroic devices are much more energy efficient, less noisy, compact, and light-weight. The magneto electric effect can be realized in multiferroic composites through a strain/stress mediated interaction [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] which enables effective energy transfer between electric and magnetic fields and leads to important new functionalities and new devices. A key component for reconfigurable RF/microwave electronics is a voltage tunable inductor.…”
Section: Multiferroic Thin Film Devicesmentioning
confidence: 99%
“…97 This represents a promising new approach to build a new class of fast electric field tunable low power devices based on converse ME interactions. [24][25][26]97,98 An electric field E applied to the piezoelectric transducer produces a mechanical deformation that couples to the ferrite and produces a change in the ferromagnetic resonance field, ferromagnetic resonance frequency, or permeability. Unlike the situation when magnetic fields are used for such tuning, the voltage tuning process is fast, and power efficient as the biasing voltages involve minimal currents and are nearly passive.…”
Section: Voltage Tunable Magneto-electric Rf/microwave/millimeter Wavmentioning
confidence: 99%
See 1 more Smart Citation